Hyperandrogenic athletes: performance differences in elite-standard 200m and 800m finals - Betancurt, J. O.; Zakynthinaki, M. S.; Martinez-Patiño, M. J.; Cordente Martinez, C. (Journal of Sports Sciences, 2018)
The purpose of this study was to examine whether the difference in elite-standard track and field performance between women athletes with and without hyperandrogenism reaches the 10-12% difference in performance between men and women, using only results from elite-standard track and field final competitions. Officially available data from two hyperandrogenic women (Caster Semenya and Dutee Chand) were compared with the characteristic performance of 200m and 800m elite-standard finals. The finishing times of Caster Semenya, before her ineligibility to compete in 2009 and after the suspension of the 2011 IAAF Hyperandrogenism Regulations were found to be respectively 1.24% and 1.49% faster than the predicted performance in 800m finals. When compared with the result of the second classified, the difference was respectively 0.65% and 2.08%. The analysis of the finishing times of Dutee Chand did not lead to any conclusions due to the lack of available data. The present study indicates that the percentage difference in performance between women with and women without hyperandrogenism does not reach the 3% difference requested by the Court of Arbitration for Sport for the reinstatement of the Hyperandrogenism Regulations, neither does it reach the 10% accepted range of difference in performance between men and women.